CyPhyR: a cyber‐physical analysis tool for measuring and enabling resiliency in microgrids. Issue 4 (20th May 2019) - Venkataramanan, Venkatesh; Hahn, Adam; Srivastava, Anurag
Abstract : This study presents a tool to study the cyber‐physical resiliency (CyPhyR) of critical energy infrastructure system, in particular the effect of cyber attacks on the microgrid's resiliency. The developed tool enables measuring resiliency using data from cyber and physical systems and suggests control decisions for resilient planning and operation of the microgrid. The microgrid resiliency is formulated based on graph theory based indices and cyber‐power system characteristics. A Common Vulnerability Scoring System based metric called the Cyber Asset Impact Potential is developed and used in the planning phase, and another metric, Cyber Impact Severity is introduced to study the system performance in the operational phase. The information from these two phases is provided to the operator to make informed and proactive decisions to ensure the resilient operation of the microgrid. The performance of the developed tool has been tested using comprehensive real‐time cyber‐power testbed for a Consortium for Electric Reliability Technology Solutions microgrid test system.